Patterns of Boarding School Partnerships in Education Financing at Nurul Islam Private Schools in Mataran City - Mukmin Mukmin; Muntari Muntari; Mohammad Mustari; Fahruddin Fahruddin; Muhammad Makki (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to analyse the partnership pattern in financing education at Pondok Pesantren Nurul Islam, Mataram City, in the period 2023-2024. Using a qualitative approach, this research includes data collection techniques, data condensation, data presentation, and conclusion drawing/verification to gain an in-depth understanding of the financing strategies applied. The results showed that Pondok Pesantren Nurul Islam has successfully developed a multisector partnership model to support the sustainability of education financing. Various funding source diversification strategies are implemented to reduce dependence on a single funding source. Among other things, the pesantren raises donations through a crowdfunding platform that allows broad community participation. In addition, cooperation with local and national companies contributes through corporate social responsibility (CSR) programmes, which support education funding while improving the quality of pesantren facilities and infrastructure. The scholarship programme is one of the key strategies in supporting access to education for underprivileged students, with funding from non-governmental institutions as well as the government. This partnership model not only adds to the sustainability of funding, but also strengthens the pesantren's relationship with various sectors, including government, private, and community. With these various partnership schemes, Pondok Pesantren Nurul Islam demonstrates its adaptability to economic challenges in education financing. A deeper analysis reveals that these multi-sector partnerships play an important role in strengthening the financial stability of the pesantren, as well as improving the quality of education that can be offered to santri. Through innovations in financing patterns and partnerships, Pondok Pesantren Nurul Islam has succeeded in creating a more independent and sustainable financing ecosystem, making it a model for other pesantren in developing strategic partnerships for education.